Qualitative Analysis of Cinnamomum burmannii Content using GCMS (Gas Chromatography Mass Spectometry) Method - Hayati; Jusak Nugraha; Bambang Purwanto; Hari Basuki Notobroto; Yoes Prijatna Dachlan; Hari Setiono; Idha Kusumawati (Institute of Medico-legal Publications Pvt Ltd, 2022)
To identify the bioactive compounds in Cinnamomum burmannii and their biological activity. Cinnamonbark originating from Batu Malang, East Java, which was located 700-1300 meters above sea level, wasprocessed into dry extract by maceration method with 96% ethanol solvent. Furthermore, cinnamonethanol extract was analyzed using the GCMS method to look at the content of the bioactive componentfor further testing biological activity with the server Way2Drug PASS. GCMS results showed 40 activecompounds such as trans-cinnamaldehyde, trans-anethole, cinnamyl acetate, calacorene, cadina-1,4-diene, delta-cadinene. Furthermore, of the 40 compounds, the biological activity potential was testedfor 29 bioactive compounds based on PA (probable to be active) values predicted by the Way2DrugPASS server. Cinnamomum was tested against the potential as anti-fungi, anti-bacterial, anti-oxidant,anti-inflammatory, anti-diabetic, anti-neoplastic. Trans-cinnamaldehyde showed PA 0,583 as antiinflammatory, L-limonene PA0,818 as anti neoplastic, Tans-anethole PA 0,614 as anti neoplastic,Cinnamyl acetate PA 0,669 as anti inflammatory, calacorene PA 0,698 as anti inflammatory, DeltacadinenePA 0,651 as anti neoplastic, , Cathechin PA 0,828 as anti oxidant, alpha.-Cubebene PA 0,888 asanti inflammatory and PA 0,837 as anti neoplastic, melilotin PA 0,929 as anti neoplastic, CaryophyllenePA0,915 as anti neoplastic. Cinnamomum burmannii had biological potency based on potential activity(PA) 0,432 (+0,117) as antifungi, PA 0,335 (+0,090) as antibacterial, PA 0,304 (+0,199) as antioxidan,PA 0,561 (+0,190) as anti inflammatory, PA 0,373 (+0,170) as antidiabetic, PA 0,584 (+0,234) asantineoplastic.